Roman History. (25th March 2015) - Unknown
Abstract : I begin this review with a mega biblion that will be hugely welcomed by Roman historians of all stripes: Tim Cornell and his team's long-awaited new edition of the fragments of the Roman historians, featuring more than one hundred Roman writers of history, biography, and memoir. Cornell and his team have replaced the long-outdated edition of Hermann W. G. Peter with a state-of-the-art three-volume work. The first volume provides an excellent and comprehensive guide to the authors; the second features the parallel texts themselves, alongside new translations; the final volume comprises the commentary, plus the necessary concordances and indices. The clear layout makes it easy to match up the introductions to each author, their testimonia and fragments, and then the related commentary. The selection and presentation of the Roman authors is careful: the introduction describes the aim to present all that is known about the authors and their work but also emphasize 'the limits of our knowledge' (7). This is clearly a more conservative selection than before (and rightly so; the thirty-six Historia Augusta 'historians', for instance, are relegated to their own appendix). The coverage is broadly chronological, ending in the third century (which is of course slightly disappointing for those interested in the rich body of late Roman historiography). This is clearly a landmark achievement, and it is especially to be welcomed that it is unusually user-friendly, for students as well as for scholars. Another point might be of interest: out of the 111 Roman authors (or groups of authors) featured there is but one woman: Agrippina the Younger (no. 77), whose memoirs were cited by both Tacitus and Pliny the Elder. Of the ten historians involved in this project, incidentally, just one is a woman. These figures have led me to consider the gender ratio of the books under review this time and the results are striking: out of the sixteen books under review, just three have female authors.